2019
DOI: 10.5430/jnep.v9n7p128
|View full text |Cite
|
Sign up to set email alerts
|

Improving nursing student cultural competence: Comparing simulation to case-based learning

Abstract: Background: Cultural competence encompasses knowledge, skills, and comfort in caring for patients from diverse cultures and is a core competency in providing patient-centered care. Simulation provides an opportunity to expose students to diverse cultures. Case-based learning has been effective in improving nursing student communication and problem-solving skills, but no research describes its use in cultural education. The purpose of this study was to compare the effect of simulation to case-based learning on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Of the more methodologically rigorous designs, four treatment control-designed studies showed no statistically significant changes regardless of the number of SPs and the duration of the simulation (Byrne, 2020;Chung & Jarvill, 2019;Garrido et al, 2014;Hamilton, 2016). The scores of the 10 studies, based on the Joanna Briggs Institute Critical Appraisal Checklist for Randomized Controlled Trials and Quasi-Experimental Studies ranged from 44.4% (Harder, 2018) to 100% (Byrne, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the more methodologically rigorous designs, four treatment control-designed studies showed no statistically significant changes regardless of the number of SPs and the duration of the simulation (Byrne, 2020;Chung & Jarvill, 2019;Garrido et al, 2014;Hamilton, 2016). The scores of the 10 studies, based on the Joanna Briggs Institute Critical Appraisal Checklist for Randomized Controlled Trials and Quasi-Experimental Studies ranged from 44.4% (Harder, 2018) to 100% (Byrne, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Garrido et al (2014) reported on second-year graduate students. Participants in 3 studies received cultural education during regular course work prior to beginning simulation and the use of SPs (Byrne, 2020;Chung, & Jarvill, 2019;Hamilton, 2016). There was only one study that used SPs in a practicum course of patients' health care problems (Garrido et al, 2014).…”
Section: Sample Sampling and Measurementmentioning
confidence: 99%
See 3 more Smart Citations